Role of Epigenetic Mechanisms in Oral Health: A Review - Juneius, C. Elizabeth Rani (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To review the literature on the oral health status of the population, evidence-based understanding of epigenetic mechanisms, and its significant role in diseases occurring in the oral cavity. Background: Epigenetics is the study of heritable changes in gene expression that does not involve changes to the underlying DNA sequence. In other words, it is a change in phenotype without a change in genotype, which in turn affects the way cells read genes. Epigenetic change is a regular and natural occurrence but can also be influenced by several factors including age, the environment/lifestyle, and disease state. The field of epigenetics is quickly growing, and it is believed that both the environment and lifestyle can interact with the genome to influence epigenetic change. These changes may be reflected at various stages throughout a person’s life and even in later generations. Conclusion: Epigenetic codes help us understand the biological phenotype that arises from the interaction of the human genome with the environment in health and in disease. Epigenetics is a major turn away from molecular biology. Current epigenetics not only offers new insights into gene regulation and heredity, but also it challenges the way we think about evolution, genetics, and development. Most interestingly, it suggests testable mechanisms whereby environmental factors (ranging from stress to infection) can influence genetic expression.